Demagnetization through level crossing: The effect of charge fluctuations. - Wio, Horacio Sergio; López, A.; Alascio, Blas Rafael (North Holland Publishing Co., 1978)
Fil: Wio, H. S. Comisión Nacional de Energía Atómica; Argentina